The Effect of Digital Mindset on Online Purchase Decision: The Moderating Role of Generational Difference among Wardah Colorfit Matte Foundation Consumers - Dewi, Aprillya Mutia; Kurnia, Dede; Yusup, Ismail (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
Digital transformation has changed the way consumers search for product information, evaluate alternatives, and make purchase decisions in e-commerce. However, the availability of digital information does not always lead to actual purchase decisions, as shown in the case of Wardah Colorfit Matte Foundation on Shopee, which has high ratings and many reviews but relatively lower sales than other Wardah complexion products. This study aims to analyze the effect of Digital Mindset on Online Purchase Decision and examine the moderating role of Generational Difference. This study used a quantitative method with an associative-causal and moderation approach. Data were collected through a structured questionnaire using a five-point Likert scale. The sample consisted of 370 Generation X and Generation Y consumers who had searched for information or purchased Wardah Colorfit Matte Foundation through Shopee. Data were analyzed using descriptive analysis and PROCESS Macro Model 1 with 5,000 bootstrap resamples. The results show that Digital Mindset has a positive and significant effect on Online Purchase Decision. Generational Difference also significantly moderates this relationship, with a stronger effect found among Generation Y than Generation X. These findings indicate that online purchase decisions are influenced not only by marketplace information, but also by consumers’ internal digital readiness and generational characteristics. The study suggests that Wardah Cosmetics should develop generation-based digital marketing strategies to improve consumer purchase decisions in beauty e-commerce.